1966
DOI: 10.1677/joe.0.0340163
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oestrogen: Androgen Interaction on the Reticulo-Endothelial System and Reproductive Tract

Abstract: 1) Oestrone, oestriol, 17\g=b\-oestradiol,ethinyloestradiol, oestradiol monobenzoate, diethylstilboestrol, 4-hydroxy-\g=a\,\g=b\-diethyldibenzyl(HDB), dienoestrol, hexoestrol, triphenylethylene and tri-p-anisylchloroethylene (TACE) stimulated the reticulo-endothelial system (RES) in intact male and in ovariectomized female mice.(2) Testosterone propionate inhibited the vaginal smear response to all the above oestrogenic compounds. It also inhibited the RE stimulation produced by oestrone, oestriol, ethinyloest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

1966
1966
1985
1985

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
2
5
1
Order By: Relevance
“…Oestriol and 17a-ethynyl-19-nortestosterone have no effect on the RE stimulation produced by 17/?-oestradiol, but both compounds inhibit the RE stimulant effect of diethylstil¬ boestrol. Testosterone and progesterone did not inhibit the RE stimulant effects of 17/?-oestradiol and diethylstilboestrol-in fact, testosterone potentiated the stimulant effect of 17/?-oestradiol on the RES which confirms previous findings (Nicol et al , 1966. MER-25 depressed the RE stimulant effects of both 17^-oestradiol and diethylstilboestrol to the level of the untreated controls.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Oestriol and 17a-ethynyl-19-nortestosterone have no effect on the RE stimulation produced by 17/?-oestradiol, but both compounds inhibit the RE stimulant effect of diethylstil¬ boestrol. Testosterone and progesterone did not inhibit the RE stimulant effects of 17/?-oestradiol and diethylstilboestrol-in fact, testosterone potentiated the stimulant effect of 17/?-oestradiol on the RES which confirms previous findings (Nicol et al , 1966. MER-25 depressed the RE stimulant effects of both 17^-oestradiol and diethylstilboestrol to the level of the untreated controls.…”
Section: Discussionsupporting
confidence: 87%
“…The effects of oestrogen : androgen interaction on the RES have already been described (Nicol et al 1966). It was shown that testosterone has no effect on the RE stimulation produced by the stilbene-type of oestrogen, but strongly potentiates the RE-stimulant effect of 17/?-oestradiol.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations